(untitled) (Bangladesh Journal of Plant Taxonomy, 2014)
Sixteen species of the tribe Merremieae Austin (Convolvulaceae) from India were morphometrically analyzed with the help of Principal component analysis (PCA) and cluster analysis to explain the relationship between them. PCA showed that quantitative characters like corolla breadth, fruit breadth and length of paracot leaf play important role in bringing together all the species in the same tribe while the characters like leaf length, leaf breadth, petiole length, pedicel length, calyx length and calyx breadth play vital role in the delimitation of taxa within the tribe Merremieae. Cluster analysis and dendrogram revealed that, the genus Operculina S. Manso is segregated from Merremia Denns. ex Endlich.; genus Hewittia Wight. & Arn. is very close to Merremia, probably originated from M. aegyptia (L.) Urban and M. dissecta (Jacq.) Hall. f. cluster and genus Xenostegia Austin & Staples is isolated in the separate cluster. DOI: http://dx.doi.org/10.3329/bjpt.v21i2.21350 Bangladesh J. Plant Taxon. 21(2): 121-128, 2014 (December)